Metal-free regioselective cross dehydrogenative coupling of cyclic ethers and aryl carbonyls - Mane, Kishor D.; Mukherjee, Anagh; Vanka, Kumar; Suryavanshi, Gurunath (Journal of Organic Chemistry, 2019)
A highly regioselective, efficient, and metal-free oxidative cross dehydrogenative coupling (CDC) of aryl carbonyls with cyclic ethers has been developed. This method offers easy access to substituted alpha-arylated cyclic ethers with a high functional group tolerance in good to excellent yields. The regioselectivity of this CDC reaction was confirmed by density functional theory (DFT)-based calculations.

Metal-free access to hindered N-alkyl sulfoximines via in-situ generated Aza-oxyallyl cations from functionalized alkyl bromide - More, Satish G.; Mane, Kishor D.; Suryavanshi, Gurunath (Asian Journal of Organic Chemistry, 2022)
Herein, we report a catalyst-free and mild synthetic method for the construction of hindered N-alkyl sulfoximines derivative. A wide range of hindered di-alkyl sulfoximines can be readily obtained from the reaction of alpha-bromo-hydroxamates with a variety of sulfoximines, including diaryl, aryl-alkyl, di-alkyl and heteroaryl sulfoximines.
Keywords: alpha-Bromo hydroxamates; Aza-oxyallyl cations; Di-alkyl sulfoximines; metal-free; Sulfoximines